First report of dill blight in cyprus caused by Itersonilia perplexans - Samouel, Stelios; Iacovides, Tefkros A.; Kanetis, Loukas (My University, 2015)
During February 2015, an acre of commercial, open-field dill (Anethum graveolens L. cv. ‘Diana’) located near Limassol, Cyprus was severely affected by a foliar disease, rendering the produce unmarketable. The weather was atypical for the season and included abundant rainfall and prolonged cool temperatures (7 to 15°C). Initial symptoms appeared on the leaves and petioles as greyish spots. Progressively, lesion enlargement resulted in necrosis and collapse of the infected tissue, causing a foliar blight. In addition, plant stems also developed brown streaking symptoms. Isolations from the infected tissues on potato dextrose agar (PDA) resulted in flat, circular, whitish to cream-colored colonies of velvety texture with slight aerial mycelium. Light microscopic examination revealed the presence of straight, hyaline, septate mycelium and clamp connections. In addition, numerous hyaline, subglobose, ovoid to pyriform sporogenous cells were also apparent, mostly solitarily, germinating by germ tube and measuring (n = 20) 11.9 to 16.6 µm long (mean = 14.3 ± 2.3 µm) × 8.1 to 10.5 µm wide (mean = 9.2 ± 0.9 µm). Spores were ballistospores (n = 20), lemon-shaped, broadly lunate, 10.2 to 18.6 µm long (mean = 14.3 ± 3.2 µm) × 7.3 to 13.2 µm wide (mean = 10.2 ± 2.5 µm). Based on these morphological characteristics, the causal agent was identified as the basidiomycete (Tremellomycetes) Itersonilia perplexans Derx (Boekhout 1991). Furthermore, genomic DNA was extracted from infected plant tissue, and the ITS rDNA region was partially amplified and sequenced using universal primers ITS1 and ITS4 (White 1990). A consensus sequence was deposited in GenBank (Accession No. KP998125) and BLAST analysis in the NCBI database revealed 99% identity to an I. perplexans sequence (Accession No. KF780585) previously reported on the forage plant Sosnowsky’s hogweed (Heracleum sosnowskyi; Apiaceae) and to that of I. perplexans ex-type strain CBS 363.85 (Accession No. NR_077117). In a pathogenicity test, 10 potted seedlings of dill (cv. Diana) were spray-inoculated with a spore suspension (1 × 105 ballistospores/ml) from fungal cultures of the sequenced isolate grown on PDA until runoff, bagged for 24 h, and placed in a growth chamber at 25°C under constant fluorescent light. Subsequently, inoculated plants were uncovered and kept at ambient temperature (22 to 25°C). An equal number of seedlings sprayed with water and treated similarly served as control plants. Typical blight appeared 10 to 12 days after inoculation, while noninoculated plants remained disease-free. The fungus was reisolated from diseased plants but not from the control plants, thus fulfilling Koch’s postulates. I. perplexans has been reported to parasitize several plant species of the families Apiaceae and Asteraceae (Boekhout 1991; Koike and Tjosvold 2001; McGovern et al. 2006). More specifically, dill leaf blight by I. perplexans has been documented in several European countries, as well in the USA and Australasia (Boekhout 1991; Koike and Tjosvold 2001; Rodeva et al. 2009). To our knowledge, this is first report of dill blight caused by I. perplexans in Cyprus.
Keywords: Foliar disease; Weather; Streaking symptoms